Effectiveness of Flipped Learning Model in Improving Students' Critical Thinking Skill - Unga Utami; Anik Ghufron; Farida Agus Setiawati (Universitas Sebelas Maret, 2025)
The development of students’ critical thinking skills is a major priority in 21st-century education. This study examined the effectiveness of the Flipped Learning Model (FLM) in enhancing critical thinking skills among elementary school students. Using a pre-experimental one-group pre-test–post-test design, the research involved 120 students from four elementary schools. The FLM intervention integrated pre-class digital video materials and collaborative in-class learning activities, while conventional instruction relied on direct teaching methods. Students’ critical thinking skills were assessed using a validated test based on Facione’s framework, which includes the indicators of Interpretation, Analysis, Evaluation, Inference, Explanation, and Self-regulation. The results revealed a significant increase in students’ post-test scores compared to their pre-test scores (p < 0.05), indicating that FLM contributed to higher levels of critical thinking. The positive impact is attributed to the shift from teacher-centered to student-centered learning, allowing students to understand basic concepts independently before class and practice higher-order thinking during classroom activities. These findings provide important implications for teachers, curriculum developers, and policymakers in designing learning strategies that promote critical thinking and support Education for Sustainable Development. Future research is recommended to examine the long-term effects of FLM across broader cognitive outcomes and diverse educational contexts.